Strategic lines of sustainable action for health care centers in Colombian regions - Valencia Rivero, Karen Tatiana (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2021)
The Sustainable Development Goals defined by the General Assembly of the United Nations, promote an action plan for the development of social, economic and environmental aspects that should be achieved before 2030. This article seeks to analyze from a qualitative perspective sustainable strategies implemented in hospitals at different countries where sustainable strategies were implemented under different socio-economic and cultural contexts, and successfully helped to efficiently improve processes while reducing their environmental impact. Current situation of hospital sustainability at a global level will be taken as a starting point to propose strategies that allow improving health services in Colombia through the adoption of the most efficient and successful methods found, which together with Industrial and Biomedical engineering tools will open new paths to ensure a healthy life.